Histone Deacetylases: the Biology and Clinical Implication - Yao, Tso-Pang.; Seto, Edward; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The book highlights work from many different labs that taught us abnormal HDACs potentially contribute to the development or progression of many human diseases including immune dysfunctions, heart disease, cancer, memory impairment, aging, and metabolic disorders.
Keywords: Medicine; Medical genetics; Medical laboratories; Toxicology; Biochemistry; Post-translational modification of proteins; Biomedicine; Pharmacology/Toxicology.; Biomedicine general; Posttranslational Modification; Protein Science; Laboratory Medicine; Gene Function